Manipulation of insect gut microbiota towards the improvement of Bactrocera oleae artificial rearing. Issue 6 (14th June 2020) - Koskinioti, Panagiota; Ras, Erica; Augustinos, Antonios A.; Beukeboom, Leo W.; Mathiopoulos, Kostas D.; Caceres, Carlos; Bourtzis, Kostas
Abstract: Bactrocera oleae (Rossi) (Diptera: Tephritidae) is the main pest of olive trees ( Olea europaea L.), causing major damages in olive crops. Improvement of mass rearing is a prerequisite for the successful development of large‐scale sterile insect technique (SIT) applications. This can be achieved through the enrichment of artificial diets with gut bacteria isolates. We assessed the efficiency of three gut bacteria previously isolated from Ceratitis capitata (Wiedemann), and four isolated from B. oleae, as larval diet additives in both live and inactivated/dead forms. Our results showed that dead Enterobacter sp. AA26 increased pupal weight, whereas both live and dead cells increased pupal and adult production and reduced immature developmental time, indicating that its bacterial cells serve as a direct nutrient source. Live Providencia sp. AA31 improved pupal and adult production, enhanced male survival under stress conditions, and delayed immature development. Dead Providencia sp. AA31, however, did not affect production rates, indicating that live bacteria can colonize the insect gut and biosynthesize nutrients essential for larval development. Live and dead Bacillus sp. 139 increased pupal weight, accelerated immature development, and increased adult survival under stress. Moreover, live Bacillus sp. 139 improved adult production, indicating that Bacillus cells are a direct source of nutrients. Dead Serratia sp. 49 increased pupal and adult production and decreased male survival under stress conditions whereas live cells decreased insect production, indicating that the live strain is entomopathogenic, but its dead cells can be utilized as nutrient source. Klebsiella oxytoca, Enterobacter sp. 23, and Providencia sp. 22 decreased pupal and subsequent adult production and were harmful for B. oleae . Our findings indicate that dead Enterobacter sp. AA26 is the most promising bacterial isolate for the improvement of B. oleae mass rearing in support of future SIT or related population suppression programs. Abstract : Improvement of mass rearing is a necessary prerequisite for the successful development of large‐scale sterile insect applications. This may be achieved through the enrichment of artificial diets with gut bacteria isolates. In the current study, we assessed the efficiency of three gut bacteria previously isolated from Ceratitis capitata, and four isolated from the olive fruit fly, Bactrocera oleae (both Diptera: Tephritidae), as larval diet additives in both live and inactivated/dead forms, with encouraging results.